FORMATION OF MEDIA COMPETENCE IN THE PROCESS OF DISTANCE EDUCATION: FACTORS OF INFLUENCE. QUALITY - Murzina, Olena (Continuing Professional Education: Theory and Practice, 2022)
The article considers the main factors that affect the quality of distance learning in the context of media competence formation. Incompetent use of information and media technologies, lack of modern software, computer equipment and media, as well as the media competence formation in tutors and students negatively affect the quality of distance learning. Our research allowed us to identify the main factors influencing the effectiveness of the media competence formation of the teachers and students in the distance education system. The factors we have identified directly affect the quality of distance learning. Such factors include: preparation of the discipline’s content, motivation and interest of all participants in the educational process, media competence of the tutor and students, material and technical equipment of both tutor and student, factors of the media environment of higher education, factors related with individual characteristics of all participants in the educational process. We also substantiate the significance and nature of the factor we have identified that significantly affects the effectiveness of distance learning in higher education institutions. In our study it has been found that for the effective use of the media environment of a higher education institution it is necessary to have: material and technical equipment, educational content, competent tutors, means of control, technologies for using cloud technologies. Therefore, we have considered the criteria of the process of evaluating educational content, the effective use of communicative means of participants in the educational process, the professionalism of the teachers.